A COMPARATIVE STUDY OF DORZOLAMIDE + TIMOLOL VS. BRIMONIDINE + TIMOLOL FIXED COMBINATION THERAPY IN THE MANAGEMENT OF PRIMARY OPEN ANGLE GLAUCOMA - Ramniklal Savalia, Pratik (International Journal of Clinical and Biomedical Research, 2017)
Background: To compare the efficiency of dorzolamide + timolol fixed combination vs. the Brimonidine + timolol fixed combination in the management of primary open-angle glaucoma Materials and methods: A prospective study conducted over a period of 6 months with a total of 69 patients having primary open angle glaucoma (POAG) who completed a follow up of 6 months at a tertiary care hospital. Detailed history of the patient was obtained and patients were assessed for best corrected visual acuity, base line IOP with Goldmann applanation tonometer and detailed anterior and posterior segment examination. They were categorized into two groups according to the combinations prescribed by the ophthalmologist as follow: group 1-dorzolamide+timolol and group 2-brimonidine+timolol. A follow up evaluation of each patient was done at 1, 3 and 6 months after baseline visit. Results: During our study the baseline IOP for dorzolamide + timolol group was 25.7 ±4.25 mm Hg and for brimonidine + timolol group was 26.3 ±5.86 mm Hg. During 6 months treatment, the mean reduction in IOP was 7.83 mm Hg (29.4%) in dorzolamide + timolol group and 9.39 mm Hg (35.6%) in brimonidine + timolol group. Conclusion: Our study showed that brimonidine + timolol combination has superiority over dorzolamide + timolol to reduce the IOP in newly diagnosed patients with POAG The value of IOP reduction in our study in brimonidine + timolol group was 9.39 mm Hg (35.6%) and 7.83 mm Hg (29.4%) in dorzolamide + timolol group. KEYWORDS: Primary open angle glaucoma, brimonidine, timolol, dorzolamide.